The Effect of Reading Habits at Home and the Availability of Reading Materials on the Reading Literacy Ability of Sixth-Grade Students at UPT SD Negeri 1 Kulo - Asnih; Muhammad Hanafi; Yusmah; Nuraini K; Aswadi; Jamaluddin Ahmad (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study investigated the influence of reading habits at home and the availability of reading materials on the reading literacy ability of sixth-grade students at UPT SD Negeri 1 Kulo. Employing a quantitative explanatory research design, the study utilized saturated sampling involving the entire population of 23 sixth-grade students. Data were collected using questionnaires to measure reading habits at home and the availability of reading materials, along with a standardized reading literacy test. Data were analyzed using descriptive statistics and multiple linear regression with SPSS software. The results revealed that: (1) reading habits at home had a positive and significant effect on reading literacy ability (t = 3.12, p = 0.005 < 0.05); (2) the availability of reading materials also exerted a positive and significant effect (t = 2.45, p = 0.021 < 0.05); and (3) both variables simultaneously had a significant influence (F = 18.76, p = 0.000 < 0.05). The coefficient of determination (R² = 0.652) indicated that 65.2% of the variance in students’ reading literacy ability could be explained by the two variables, while the remaining 34.8% was influenced by other factors. The findings underscore the critical role of home-based reading practices and resource availability in enhancing elementary students’ reading literacy. Collaboration among parents, teachers, and schools is essential to create a literacy-rich home environment that optimally supports students’ reading development.